2021
DOI: 10.1093/ve/veab078
|View full text |Cite
|
Sign up to set email alerts
|

Intra-host evolution during SARS-CoV-2 prolonged infection

Abstract: Long-term infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) represents a challenge to virus dispersion and the control of coronavirus disease 2019 (COVID-19) pandemic. The reason why some people have prolonged infection and how the virus persists for so long are still not fully understood. Recent studies suggested that the accumulation of intra-host single nucleotide variants (iSNVs) over the course of the infection might play an important role in persistence as well as emergence of mut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 65 publications
5
40
0
2
Order By: Relevance
“…Through whole genome sequencing for SARS-CoV-2, performed at multiple time-points from the patient samples, authors demonstrated early emergence of the E484K substitution followed by N501Y, K417T, and multiple others mutation (including some novel mutations) in the spike gene and RBD. Increase in the genomic diversity reflecting intra-host evolution of SARS-CoV-2 during prolonged infection was also noted in a recent cohort study by Voloch et al 27 .…”
Section: Sequence Variation With Wt Strains and Existing Sars-cov-2 Vocs/voissupporting
confidence: 60%
See 1 more Smart Citation
“…Through whole genome sequencing for SARS-CoV-2, performed at multiple time-points from the patient samples, authors demonstrated early emergence of the E484K substitution followed by N501Y, K417T, and multiple others mutation (including some novel mutations) in the spike gene and RBD. Increase in the genomic diversity reflecting intra-host evolution of SARS-CoV-2 during prolonged infection was also noted in a recent cohort study by Voloch et al 27 .…”
Section: Sequence Variation With Wt Strains and Existing Sars-cov-2 Vocs/voissupporting
confidence: 60%
“…The speculations have also been raised that the long term persistence of SARS-CoV-2 infection in an immunocompromised subject can be a probable mechanism behind the Omicron origin. Existing literature [24][25][26][27] 25 . Authors documented long persistence of SARS-CoV-2 infection (more than six month) in a patient with advanced HIV and antiretroviral treatment failure.…”
Section: Sequence Variation With Wt Strains and Existing Sars-cov-2 Vocs/voismentioning
confidence: 99%
“…Library preparation for sequencing was performed using the TruSeq DNA Nano kit or Nextera DNA Flex kit (Illumina, USA), and viral whole-genome amplification was carried out following the Artic Network protocol ( https://artic.network/ncov-2019 ) ( 17 ). Sequencing was performed in a MiSeq system using MiSeq reagent kit v3 (Illumina, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Following these findings, current guidelines recommend discontinuation of isolation after 10 days of symptom onset, without testing ( 15 , 16 ). However, the presence of intact full-length severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) genomes in persistently positive patients has been documented previously ( 17 ), suggesting the infectious potential of these viruses ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…[61] Another challenge for a phylogenetic approach is that multiple variants may occur within an individual infection. [62] Some immunocompromised individuals have chronic infections that can last six months to a year [63] In some cases, those patients may be treated with convalescent plasma or antibodies which may be selecting for evasive mutations that are being observed. [64] During the long-term infection, a spike protein can emerge with multiple variations, which phylogenetic analysis identifies as "long branch" divergence from the phylogenetic tree.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%